Increasing rate of diagnosed childhood mental illness in the United States: Incidence, prevalence and costs - Joseph Tkacz; Brenna L. Brady (Elsevier, 2021)
Objective: This study examined the rate and economic burden of pediatric mental illness from 2012 to 2018. Study design: Observational, retrospective analysis of administrative healthcare data. Methods: This retrospective study of the MarketScan Commercial Research Database included calendar year-based samples (2012-2018) of children aged 4-17 with continuous medical, pharmacy, and mental health/substance abuse coverage for the year of interest and prior year. Incidence and prevalence rates of overall and specific mental illness diagnoses were calculated based on the appearance of diagnosis codes on claims: alcohol/substance abuse, depression, anxiety, eating disorders, bipolar, schizophrenia, developmental disorders, attention deficit/hyperactivity, and conduct disorders. Annual direct medical costs were compared between children with any mental illness and a matched non-mental illness control population. Results: Between 2.4 and 4.1 million children qualified for each calendar year sample. From 2012 to 2018, there was a 34.6% increase in the prevalence of mental illness. Attention deficit/hyperactivity, conduct disorders, anxiety, and depression were the most common conditions, while eating disorders, anxiety, and depression presented the greatest increases at 96%, 95%, and 73% respectively. Children with a mental illness incurred significantly greater medical costs compared to matched controls in all years assessed (2018 comparison: $6,055±$27,198 vs. $1,629±$7,274; p < 0.001). Conclusions: Childhood mental illness diagnoses have increased substantially in the United States from 2012 to 2018. In addition to patient impacts, mental health diagnoses also place a notable burden on the healthcare system via increased medical costs. As mental illness is known to be underdiagnosed, the true rate of mental illnesses among children is likely even greater.